Automation of quality control for Paroc Panel System / Kingspan Oy, Parainen : Automating Quality Control Processes for Paroc Panel System / Kingspan Oy in Parainen - Valde, Nicklas (My University, 2024)
This master's thesis explores the importance of quality control throughout the product lifecycle, focusing on automated methods. Automated quality control solutions available in the market provide high-quality, sustainable performance and can significantly enhance an organization's competitiveness by ensuring products meet specified requirements. Quality control systems not only improve productivity and reduce costs but also help maintain competitiveness and deliver long-term benefits, which are crucial for the Paroc Panel System's plant in Parainen. The Parainen factory, known for its production of sandwich panels, faces challenges in quality control due to its semi-automated production line that relies heavily on manual inspections. The current quality control process includes visual inspections performed by operators and laboratory tests for raw materials and finished panels. However, the effectiveness of these processes is limited by inconsistencies and manual labour demands, making it difficult to ensure consistent quality across all products. The implementation of automated quality control is proposed as a solution to address these issues, enabling the factory to improve process efficiency, reduce waste and maintain high-quality standards. The thesis emphasizes that the automated quality control system will not only ensure product quality but also align with the company's Compliance Policy, which aims to guarantee that all products meet customer expectations and regulatory standards. Additionally, automated quality control will support the company's sustainability goals by reducing waste and enhancing resource efficiency. This study presents a comprehensive analysis of the proposed improvements to the factory's quality control processes, including specific automation solutions for wool and steel inspections, glue application monitoring, and the automated quality control of finished panels. By adopting these measures, Paroc Panel System aims to enhance its production efficiency, reduce costs and strengthen its position as a leading producer in the building industry. The findings of this thesis could also offer valuable insights for the potential implementation of similar automation solutions at other production facilities within the Kingspan Group.
Keywords: Quality Control, Automation, Sustainability, Manufacturing Efficiency, Cost Reduction